Individual heat map assessments demonstrate vestronidase alfa treatment response in a highly heterogeneous mucopolysaccharidosis VII study population. Issue 1 (26th June 2019) - Haller, Christine; Song, Wenjie; Cimms, Tricia; Chen, Chao‐Yin; Whitley, Chester B.; Wang, Raymond Y.; Bauer, Mislen; Harmatz, Paul
Abstract: Mucopolysaccharidosis (MPS) VII is an ultra‐rare, progressively debilitating, life‐threatening lysosomal disease caused by deficiency of the enzyme, β‐glucuronidase. Vestronidase alfa is an approved enzyme replacement therapy for MPS VII. UX003‐CL301 was a phase 3, randomized, placebo‐controlled, blind‐start study examining the efficacy and safety of vestronidase alfa 4 mg/kg intravenously administered every 2 weeks to 12 patients with MPS VII. Due to the rarity of disease, broad eligibility criteria resulted in a highly heterogeneous population with variable symptoms. For an integrated view of the diverse data, the changes from baseline (or randomization for the placebo period) in clinical endpoints were grouped into three functional domains (mobility, fatigue, and fine motor + self‐care) and analyzed post‐hoc as subject‐level heat maps. Mobility assessments included the 6‐minute walk test, 3‐minute stair climb test, Bruininks‐Oseretsky test (BOT‐2) gross motor function subtests, and patient‐reported outcome assessments (PROs) related to movement, pain, and ambulation. Fatigue assessments included the Pediatric Quality of Life Multidimensional Fatigue Scale and other fatigue‐related PROs. Fine motor + self‐care assessments included BOT‐2 fine motor function subtests and PROs for eating, dressing, hygiene, and caregiver assistance. Most subjects showed improvement in at least one domain. Two subjects improved in two or more domains and two subjects did not show clear improvement in any domain. Both severely and mildly affected subjects improved with vestronidase alfa in clinical assessments, PRO results, or both. Heat map analysis demonstrates how subjects responded to treatment across multiple domains, providing a useful visual tool for studying rare diseases with variable symptoms.